MiR-27a-3p promotes the osteogenic differentiation by activating CRY2/ERK1/2 axis - Li-Rong Ren; Ru-Bin Yao; Shi-Yong Wang; Xiang-Dong Gong; Ji-Tao Xu; Kai-Shun Yang (BMC, 2021)
Abstract Background Osteoporosis seriously disturbs the life of people. Meanwhile, inhibition or weakening of osteogenic differentiation is one of the important factors in the pathogenesis of osteoporosis. It was reported that miR-27a-3p reduced the symptoms of osteoporosis. However, the mechanism by which miR-27a-3p in osteogenic differentiation remains largely unknown. Methods To induce the osteogenic differentiation in MC3T3-E1 cells, cells were treated with osteogenic induction medium (OIM). RT-qPCR was used to evaluate the mRNA expression of miR-27a-3p and CRY2 in cells. The protein levels of CRY2, Runt-related transcription factor 2 (Runx2), osteopontin (OPN), osteocalcin (OCN) and the phosphorylation level of extracellular regulated protein kinases (ERK) 1/2 in MC3T3-E1 cells were evaluated by western blotting. Meanwhile, calcium nodules and ALP activity were tested by alizarin red staining and ALP kit, respectively. Luciferase reporter gene assay was used to analyze the correlation between CRY2 and miR-27a-3p. Results The expression of miR-27a-3p and the phosphorylation level of ERK1/2 were increased by OIM in MC3T3-E1 cells, while CRY2 expression was decreased. In addition, OIM-induced increase of calcified nodules, ALP content and osteogenesis-related protein expression was significantly reversed by downregulation of miR-27a-3p and overexpression of CRY2. In addition, miR-27a-3p directly targeted CRY2 and negatively regulated CRY2. Meanwhile, the inhibitory effect of miR-27a-3p inhibitor on osteogenic differentiation was reversed by knockdown of CRY2 or using honokiol (ERK1/2 signal activator). Furthermore, miR-27a-3p significantly inhibited the apoptosis of MC3T3-E1 cells treated by OIM. Taken together, miR-27a-3p/CRY2/ERK axis plays an important role in osteoblast differentiation. Conclusions MiR-27a-3p promoted osteoblast differentiation via mediation of CRY2/ERK1/2 axis. Thereby, miR-27a-3p might serve as a new target for the treatment of osteoporosis.